In vitro biofilm formation and antibiotic susceptibility of Pseudomonas aeruginosa isolated from airways of patients with cystic fibrosis - Długaszewska, Jolanta; Antczak, Marta; Kaczmarek, Izabella; Jankowiak, Renata; Buszkiewicz, Malgorzata; Herkowiak, Magdalena; Michalak, Klaudia; Kukuła, Helena; Ratajczak, Magdalena (Journal of Medical Science, 2016)
Background: Pseudomonas aeruginosa is the predominant cause of airway infections in patients with cystic fibrosis (CF) as a result of its ability to form biofilm. Resistance to antimicrobial agents is the most important feature of biofilm infection. The aim of this study was to evaluate biofilm formation and to compare antibiotic susceptibility of P. aeruginosa living in two modes of growth: planktonic and biofilm, isolated from respiratory tract of CF patients. Methods: Biofilm formation and biofilm susceptibility to antibiotics were determined using modified microtitere plate method. For susceptibility testing of planktonic culture to antibiotics serial microdilution broth method were used.Results: More than 95% of isolates were capable to form biofilm. Isolates grown as biofilms were more resistant to tested antibiotics compared to those grown planktonically. Ciprofloxacin showed the highest activity against P. aeruginosa biofilm. In contrast, no bacteriostatic activity was obtain for the highest concentration of piperacillin tested against most of P. aeruginosa strains growing in a biofilm (BIC > 4096 mg/L).Conclusions: Our study indicates the need to develop a standardized susceptibility testing method for biofilm mode of growth of pathogens. It appears that it is appropriate to introduce a biofilm susceptibility testing to routinely performed tests, as the effect of antibiotics on biofilm eradication may be variable and unpredictable.
Keywords: biofilm resistance; chronic infections; susceptibility testing